2013
DOI: 10.1002/ppsc.201300224
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Magnetic Nanorods in Solidifying Films

Abstract: Magnetic nanorods offer many opportunities in manufacturing of multifunctional composites with unprecedented magnetic and mechanical properties. [1][2][3][4][5][6][7] Coating fi lms with ordered magnetic nanorods are especially attractive for different hightech applications. These fi lms provide additional functionality, for example, enabling magnetic recording or magneto-optic features. [ 4,[8][9][10] However, the strategy for nanorod alignment in the macroscopic samples has not been developed so far. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…The images of the nanorods were taken at t = 0, 1, 2, 3, and 4 s and then processed to obtain the histograms and to compare them with the theory (solid curves). Adapted with permission . Copyright 2013, Wiley‐VCH.…”
Section: Control Of Nanorod Alignment In Thin Filmsmentioning
confidence: 99%
See 3 more Smart Citations
“…The images of the nanorods were taken at t = 0, 1, 2, 3, and 4 s and then processed to obtain the histograms and to compare them with the theory (solid curves). Adapted with permission . Copyright 2013, Wiley‐VCH.…”
Section: Control Of Nanorod Alignment In Thin Filmsmentioning
confidence: 99%
“…Using this rheological equation of state, one can generalize the theory of nanorod rotation in a solidifying film by replacing the constant viscosity in the drag coefficient γ with the exponentially increasing one . The time τ 0 sets up a time scale for the nanorod rotation.…”
Section: Control Of Nanorod Alignment In Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manipulating rod-like nanoparticles, such as nanowires, with external magnetic fields has attracted extensive interests in a myriad of engineering applications in micro/nanofluidics and biomedical engineering. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] For instance, in a study of nanowire alignment in solidifying films where the fluid viscosity increased with time, it was found that a large portion of the nanowires cannot properly align due to the viscous force. Hence, by analyzing the relaxation time of a single nanowire under different viscosities, the total time required for the whole field to align can be extracted.…”
Section: Introductionmentioning
confidence: 99%